Number 11 - Coe, Jonathan (Alfred A. Knopf, 2017)
"Jonathan Coe finally provides a sequel to The Winshaw Legacy, the 1995 novel that introduced American readers to one of Britain's most exciting new writers -- an acerbic, hilariously dark, and unflinching portrait of modern society. In Number 11, Coe hasfilled his intricate plot with a truly Dickensian cast of characters. The novel opens in the early aughts with two ten-year-old girls, Alison and Rachel, and their frightening encounter with the "Mad Bird Woman," a mysterious figure who lives down the road. As the narrative progresses through time, the novel broadens in scope toward other people who are somehow connected to the two girls. We follow the trials and tribulations of Alison's mother, a has-been singer, as she competes on TV's reality hit I'ma Celebrity... Get Me Out of Here! Rachel's university mentor confronts her late husband's disastrously obsessive search for an untraceable German film he saw as a child. A young police constable investigates the seemingly accidental and unrelated deathsof two stand-up comedians. And when Rachel becomes a nanny for ludicrously wealthy family, she discovers a dark and terrifying secret lying beneath their immense mansion in London's most staggeringly expensive neighborhood. Combining psychological insight, social commentary, vicious satire, and even surrealist horror, this highly accomplished work holds a revealing and disquieting mirror up to the world we live in today"--